Analisis Konstitusional Terhadap Teori Asas Kesalahan Pertanggungjawaban Dokter: Studi Atas Putusan Mahkamah Agung Nomor 79 PK/PID/2013 - Iswantoro Iswantoro; Irmanjaya Thaher; Dyah Budi Asri (Jurnal Ragam Pengabdian, 2026)
This study aims to constitutionally analyze the application of the fault liability principle in doctors’ criminal responsibility based on Supreme Court Decision No. 79 PK/PID/2013. The main issues concern how law functions to limit state power legitimacy through the application of fault liability and how to address weak checks and balances mechanisms in protecting constitutional rights. This research employs a normative legal method with statutory, conceptual, and case approaches. The findings indicate that the application of the fault principle in the decision shows interpretative inconsistency, potentially blurring the distinction between professional error and medical risk. This condition contributes to the criminalization of medical professionals and weakens constitutional protections. Furthermore, weak checks and balances in the judicial system lead to dominant judicial interpretations that are not fully aligned with the rule of law. In conclusion, strengthening the evidentiary standard based on reasonable care and reforming judicial oversight mechanisms are essential to ensure legal certainty and constitutional protection for medical professionals.